Role of Edible Collagen Coating in Preserving the Chemical Quality of Hasoom (Sillago sihama) Fish During Frozen Storage - Abdullah, Ilham (Iraqi Journal of Aquaculture, 2025)
The study had Sillago sihama fish obtained from the Al-Faw city, situated at the southern boundary of Basra province. The fish were treated with collagen derived from the fish residue, the skin of Scombromorus commerson, before being frozen at -18°C for a period of 120 days. Chemical analysis of the fish, done after the freezer storage, entailed the assessment of pH, volatile nitrogenous bases, levels of free fatty acids, thiobarbituric acid, and fluid loss. The findings were indicative of an increase in the pH level of the coated and uncoated fish, although the latter registered a higher percentage at 13.6% compared to the former at 10.24%. The highest content of volatile nitrogenous bases was found in the coated fish at 74.404%, higher than the uncoated fish at 74.193%. The free fatty acid percentage for the uncoated and coated fish stands at 83.827% and 58.333%, respectively. (TBA) values also showed the highest increase in uncoated fish 85.610 % and the lowest in coated fish 63.390%, with significant differences (p<0.05) between freezing periods 60, 90, and 120 days in uncoated samples. Drip loss increased in uncoated frozen fish, reaching 44.920 %, while coated frozen fish showed a lower drip loss of 24.241%. In conclusion, the current study demonstrated the potential of collagen edible coatings in reducing oxidative changes, extending shelf-life, and preserving the quality of frozen fish.